269 Tumoral and peripheral landscape of Viral- versus Carcinogen-Driven Head and Neck Cancer. (9th November 2020) - Tan, Tze Heng; Sridhar, Sriram; Angell, Helen; Jones, Emma; Raymond, Amelia; Willis, Sophie; Polychronopoulos, Dimitris; Yovine, Alejandro; Morsli, Nassim; McCoon, Patricia; Barrett, Carl; Ascierto, Maria
Abstract : Background: Head and neck squamous cell carcinoma (HNSCC) is composed of a heterogeneous group of tumors arising trough environmental carcinogens or infection by human papillomavirus (HPV). Treatment interventions such as immunotherapy and targeted therapy have shown clinical benefit in HNSCC patients. Despite these encouraging results, resistance to treatment is still observed in the majority of patients. Additionally, clinical effectiveness of treatment options has also been shown to be associated with HPV status. Here we investigate the tumoral and peripheral landscape of HPV(-) vs. HPV(+) head and neck cancers to identify features able to expand treatment options for patients with Viral- and Carcinogen-Driven Head and Neck Cancer. Methods: Biopsies and serum samples derived from 502 primary and metastatic HNSCC patients were leveraged for genomic, proteomic and immunochemistry evaluations. Tumor biopsies from HNSCC patients commercially obtained (n=143) or derived from patients enrolled in CP1108 trial (n=19, NCT01693562 ) were profiled by gene expression. Primary tumor biopsies (N=198) from HNSCC have been assessed by Whole Exome Sequence (WES). Expression of immune markers including CD8, NKp46 was evaluated by immunohistochemistry (IHC) on 186 and 214 tumors biopsies, respectively. The expression of 80 immune related soluble factors was evaluated in serum derived from n=285 patients of HNSCC enrolled in EAGLE (NCT02369874 ), a randomized, open-label, study assessing Durvalumab and Tremelimumab vs. Standard of Care (SoC). Statistical comparison between HPV(+) vs. HPV (-) samples were conducted using R software. Results: Patients with HPV(-) vs. HPV(+) HNSCC were characterized by worse prognosis. Increased levels of immunosuppressive factors including VEGF (p=0.01), IL-8 (p=0.02), IL6 (p=0.07) and macrophages chemo attractive factor CCL4 (p=0.07) was observed in the serum of HPV(-) vs HPV(+) HNSCC patients. In the tumor microenvironment, higher mRNA expression of immune signatures associated with MDSC, Cancer Associated Fibroblast (CAF), and Metalloproteinase (MMP) was observed in HPV(-) vs. HPV (+) HNSCC patients. In contrast, HNSCC HPV(+) patients were characterized by increased mRNA expression of DC signatures and IFNg related genes (i.e. CXCL9). No differential infiltration of T and NK cells (CD8+ and NKp46+) were found in HPV (-) vs. HPV(+) patients. Enrichments of mutations in EGFR, and DNA repair genes (PMS1, POLK, ATM) was observed in HPV(+) patients. On the contrary, enrichments of mutations in TP53 was observed in HPV(-) patients. Conclusions: Deep evaluation of tumoral and peripheral landscape of viral- versus carcinogen-driven HNSCC might help understanding differential outcome of treatments regimens in HPV(+) vs HPV (-) HNSCC thus leading to novel therapeutic interventions. Trial Registration: NCT01693562, NCT02369874 Ethics Approval: The study was approved by Astrazeneca. Consent: Patients provided written consent to perform evalutions here described.